Fireweed, roseroot, Bergenia and chokeberry – joint research for supporting the herb production - Kauppinen, Sanna; Galambosi, Bertalan; Luke / Luonnonvarat ja biotuotanto / Tuotantojärjestelmät / Ekologinen kasvintuotanto (4100100212); 4100100212
In this publication you find the main results of the project called ”Special crop education for economic development in North-West Russia and South-East Finland SPECICROP”. These results concern the fermentation methods of fireweed and Bergenia leaves, measurements of active substances of different roseroot strains, the effect of Bergenia leaf extract for the endurance of sportsmen, the effect of chokeberry for blood pressure and inflammatory factors and the development of herb production in Leningrad area and Finland. Infusion from fermented Epilobium angustifolium L. leaves (Ivan tsay, Koporye tea) is traditionally consumed in Russia for the treatment of stomach ulceration, gastritis, and sleeping disorders. The traditional production method of Ivan tea includes of several labour-consuming steps. During 2012–2014 in the frame of SPECICROP project a semi-industrial fermentation process of shoots of fireweed was studied. On the base of these experiments we concluded that there is a possibility to produce Ivan tea commercially from a 40 cm shoot yield instead of leaves. The steps and the optimized parameters of the process are described on the proposed technological recommendation. The production process can be reproduced in the conditions of small-scale enterprises. During the domestication experiments of Rhodiola rosea, a collection of roseroot strains from different geographical origins was created at Mikkeli, South-East Finland. The aims of this study was to compare the root biomass and salidroside and total rosavin contents of different accessions and to choose the best accessions for further propagation. Six accessions containing high salidroside and total rosavin contents were chosen for saving in the official Finnish medicinal plant gene collection. The leaves of the commonly known decorative perennial, Bergenia species have several interesting biological activities. The green leaves contain arbutin up to 22% (d.w.), a compound, which is used in cosmetic industry as a skin-whitening agent in humans. ...